Laparoscopic diaphragmatic plication for paralysis posterior to trauma. Case report - Reyna Sepúlveda, Francisco J.; Vásquez Fernández, Francisco; Rodríguez Briseño, José Ángel; Moreno Cantú, Carlos Alberto; Muñoz Maldonado, Gerardo Enrique (UANL. Facultad de Medicina, 2016)
Diaphragmatic paralysis is a pathology characterized by the elevation of a plastic and inactive atrophic diaphragm, followed by an injury to the spinal column or to the phrenic nerve. Because it involves the phrenic nerve, it is often associated with an injury at its exit in the spinal cord at the radicular level, at the conduct or in the peripheral nerve. Clinical case: A 50-year-old male patient with a history of thoracic trauma and diagnosis of unstable thorax is admitted for progressive dyspnea in the following 8 months. Diaphragmatic paralysis is diagnosed and a laparoscopic diaphragmatic plicature is performed. Patient improved his clinical status by 29%. Discussion: The consequences of the elevation of a hemidiaphragm can be respiratory, causing hypoxemia and decreases in the ventilation---perfusion ratio. This procedure is considered a corrective surgery from the morphological and functional point of view. Conclusions: Our patient’s clinical status improved according to the Saint George respiratory questionnaire, thanks to an improved perfusion of the basal lung expansion. Laparoscopic diaphragmatic plicature is a safe procedure associated with a minimal hospital stay, and more cases need to be reported. This is the procedure of choice in our institution.